2014
DOI: 10.1007/s40261-013-0161-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Drug Interactions of Afatinib with Rifampicin and Ritonavir

Abstract: Coadministration of potent P-gp modulators had no clinically relevant effect on afatinib exposure. Effects of potent P-gp inhibitors were minimal at higher afatinib doses and can be readily managed by the timing of concomitant therapy. As afatinib is not a relevant modulator or substrate of cytochrome P450 enzymes, the drug-drug interaction potential is considered to be low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 21 publications
3
45
0
1
Order By: Relevance
“…Furthermore, it has been suggested that rifampicin activates P-gp in vivo and in vitro [11,12]. Although there are some other studies about the effects of P-glycoprotein modulation on the bioavailability of several drugs [16][17][18], to best of the authors' knowledge, this is the first study to investigate the effects of P-gp-inhibiting and -activating drugs on the intestinal absorption of immunosuppressive drugs.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, it has been suggested that rifampicin activates P-gp in vivo and in vitro [11,12]. Although there are some other studies about the effects of P-glycoprotein modulation on the bioavailability of several drugs [16][17][18], to best of the authors' knowledge, this is the first study to investigate the effects of P-gp-inhibiting and -activating drugs on the intestinal absorption of immunosuppressive drugs.…”
Section: Discussionmentioning
confidence: 91%
“…Inhibitors of P-gp, such as ritonavir can increase concentrations of afatinib, while inducers of P-gp reduce afatinib levels. The clinical consequences of concurrent use of afatinib with P-gp inducers/inhibitors are questionable, and these drugs can be administered 6-12 hours apart to avoid significant interactions [85].…”
Section: Clinical Safetymentioning
confidence: 99%
“…These preclinical data suggested the potential for afatinib to offer clinical benefit to patients with ErbB Family-driven tumours. Overall afatinib has a low potential for drug-drug interactions [67]. Afatinib is not metabolised but enzyme-catalysed metabolic reactions and is not an inhibitor or an inducer of the CYP enzymes [67].…”
Section: Afatinibmentioning
confidence: 99%
“…Overall afatinib has a low potential for drug-drug interactions [67]. Afatinib is not metabolised but enzyme-catalysed metabolic reactions and is not an inhibitor or an inducer of the CYP enzymes [67]. In vitro studies have shown that afatinib interacts with the drug transport systems involving p-glycoprotein (P-gp) and Phase I studies support the adjustment of afatinib dose as tolerated in patients requiring coadministration of P-gp inhibitors/inducers [67,68].…”
Section: Afatinibmentioning
confidence: 99%
See 1 more Smart Citation